P231 The first case of neonatal fungemia caused by Aureobasidium melanogenum. (20th September 2022) - M., Kavya; Samaddar, Arghadip; Sharma, Anuradha; Gupta, Neeraj
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Background: Aureobasidium melanogenum is a ubiquitous, saprophytic, dematiaceous fungus commonly isolated from environmental sources. It has the highest virulence potential among all Aureobasidium species and is implicated in catheter-related infections, particularly in immunocompromised hosts. Case Report: A 6-day-old female child was admitted to the neonatal intensive care unit (NICU), AIIMS, Jodhpur with respiratory distress, hypotension, bradycardia, and sepsis. The baby was preterm with a very low birth weight (1140 g) and was born to a 34-year-old G3P1A2 mother at 30 weeks gestation by elective caesarian section at a private hospital. The mother had a primary ovarian failure and had a history of spontaneous abortions for two consecutive times following in vitro fertilization. She also had a history of gestational diabetes mellitus and pregnancy-induced hypertension, for which she was on medication. At birth, the baby had respiratory distress (Apgar scores were 6 and 7 at 1 and 5 minutes of life, respectively), for which she was shifted to NICU and intubated. On day 2, she developed hypotension, bradycardia, hypocalcemia, and sepsis with deranged coagulation profile, for which she received inotropes, broad-spectrum antibiotics, fluconazole, and fresh frozen plasma. On day 3, the baby developed chest retractions and seizure-like episodes with intermittent myoclonic jerks and was started on anti-epileptics. She had persistently raised serum urea, creatinine, and C-reactive protein from day 3 of life. Due to clinical deterioration, she was shifted to AIIMS NICU for further management where she was continued on inotropes, broad-spectrum antibiotics, and fluconazole. After 46 h of admission at AIIMS NICU, the baby developed hypotension with cold extremities, feeble pulses, and increased ventilatory requirements. Chest X-ray showed bilateral diffuse infiltrates suggestive of acute respiratory distress syndrome. Culture of tracheal aspirate yielded Klebsiella pneumoniae, sensitive to piperacillin/tazobactam, amikacin, and carbapenems. The patient was started on intravenous meropenem and colistin. Blood culture showed growth of Gram-positive budding yeast cells after 48 h of incubation (Fig. 1). Subculture on Sabouraud dextrose agar revealed yeast-like colonies, initially cream-colored, becoming dark-brown with an olive-green feathery margin (Fig. 2a). Microscopically, the isolate had septate pigmented hyphae with ellipsoidal hyaline conidia (Fig. 2b). The morphologic features were consistent with Aureobasidium species. Sequencing the internal transcribed spacer region of rDNA confirmed the identity of the isolate as A. melanogenum. Antifungal susceptibility testing revealed the following MICs: amphotericin B, 0.5  μ g/ml, itraconazole, 0.25  μ g/ml, voriconazole, 0.125  μ g/ml, fluconazole, 16  μ g/ml, and caspofungin, 0.25  μ g/ml. Despite maximum inotropic and ventilatory support, the baby had persistent desaturations and hypoxia and developed multiple organ dysfunction syndrome, following which she succumbed to death on day 3 of admission to AIIMS. Conclusion: This is the first documented case of neonatal fungemia caused by the emerging yeast A. melanogenum . The patient had multiple arterial and intravenous catheters and this could be the portal of entry of the pathogen. Accurate identification is crucial for initiating appropriate antifungal therapy. Physicians should be mindful of possible A. melanogenum infection in patients with risk factors, and provide appropriate antifungal therapy with the removal of indwelling catheters whenever possible.